2019
DOI: 10.1039/c9an01702j
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine analysis on a countable number of molecules from living single cells on nanofluidic devices

Abstract: Analysis of a countable number of protein molecules released from living single cells was realized by a micro/nanofluidic device entirely integrating cellular processing and molecular processing into pL-microchannels and fL-nanochannels, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…Therefore, it is concluded that the proposed bonding process was successfully applied to the micro/nanofluidic device made of fused-silica and borosilicate glass, and the device had a pressure resistance higher than 600 kPa. Micro/nanofluidic devices fabricated by the proposed bonding process can be used for various microfluidic applications [ 1 , 2 ], nanofluidic applications with pressure-driven flows generated by high external pressures on the order of 100 kPa, such as single-molecule immunoassays [ 6 ], femtoliter solvent extraction [ 8 ], and single-cell target proteomics [ 9 ], and other nanofluidic applications such as electrophoretic single-molecule sorting [ 5 ] and miniaturized fuel cells [ 10 ]. In addition, the construction of devices made of fused-silica and borosilicate glass enables a combination of micro/nanofluidics and advanced optical microscopy such as super-resolution microscopy [ 36 , 37 ] without a reduction in performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is concluded that the proposed bonding process was successfully applied to the micro/nanofluidic device made of fused-silica and borosilicate glass, and the device had a pressure resistance higher than 600 kPa. Micro/nanofluidic devices fabricated by the proposed bonding process can be used for various microfluidic applications [ 1 , 2 ], nanofluidic applications with pressure-driven flows generated by high external pressures on the order of 100 kPa, such as single-molecule immunoassays [ 6 ], femtoliter solvent extraction [ 8 ], and single-cell target proteomics [ 9 ], and other nanofluidic applications such as electrophoretic single-molecule sorting [ 5 ] and miniaturized fuel cells [ 10 ]. In addition, the construction of devices made of fused-silica and borosilicate glass enables a combination of micro/nanofluidics and advanced optical microscopy such as super-resolution microscopy [ 36 , 37 ] without a reduction in performance.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the field has been further downscaled to nanofluidics, exploiting volumes of attoliters to femtoliters where surface effects are dominant [ 4 ]. Novel applications have been reported such as single-molecule sorting [ 5 ] and analysis [ 6 ], high-efficiency separation utilizing solid/liquid [ 7 ] and liquid/liquid phases [ 8 ], single-cell proteomics [ 9 ], and autonomous solar-light-driven fuel cells [ 10 ]. To realize these devices, micro/nano fabrication technologies are important.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By performing an on-chip ELISA, interleukin (IL)-6 cytokines secreted by a single B cell were detected at a sensitivity of five molecules. 81 The utilization of the on-chip ELISA is advantageous since it provides the necessary specificity and the versatility and nearly single-molecule sensitivity. 82 The same enzymatic reaction can be applied for the detection of various analytes by changing only the recognition molecule.…”
Section: Applicationsmentioning
confidence: 99%
“…1 Recently, the field has downscaled to nanospaces with ultrasmall volumes (aL to fL) to realize novel analytical applications such as high-efficiency chromatography, 2,3 singlemolecule detection 4 and sorting, 5 and living single-cell protein analyses. 6 Generally, for designing the analytical devices based on micro/nanofluidics, the flow rate in fluidic channels is an important parameter to calculate volumes of samples and reagents in chemical processing. Due to significantly increased fluid resistance of nanochannels compared with that of the microchannels, nanofluidic devices have employed fluidic control by an external pressure or an external voltage, 3,5,6 rather than that by a syringe pump.…”
Section: Introductionmentioning
confidence: 99%